1995
DOI: 10.1016/0896-6273(95)90104-3
|View full text |Cite
|
Sign up to set email alerts
|

Topology of the pore-region of a K+ channel revealed by the NMR-derived structures of scorpion toxins

Abstract: The architecture of the pore-region of a voltage-gated K+ channel, Kv1.3, was probed using four high affinity scorpion toxins as molecular calipers. We established the structural relatedness of these toxins by solving the structures of kaliotoxin and margatoxin and comparing them with the published structure of charybdotoxin; a homology model of noxiustoxin was then developed. Complementary mutagenesis of Kv1.3 and these toxins, combined with electrostatic compliance and thermodynamic mutant cycle analyses, al… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

20
299
0
1

Year Published

1997
1997
2008
2008

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 268 publications
(320 citation statements)
references
References 28 publications
20
299
0
1
Order By: Relevance
“…However, we expected this behavior because the orientation of the channel in mitochondria is the same as in the plasma membrane as suggested by the sensitivity of the mitochondrial channel to MgTx (13). Previous studies indicated that the binding of the highly specific Kv1.3 inhibitor toxin (e.g., MgTx), which docks in the outer-facing vestibule of Kv1.3, is pH dependent, and that protonation of Histidine 404 of Kv1.3 weakens the pore-toxin interaction (18). Accordingly, the IC 50 of GST-Bax increased from 4 to 12 nM when the bath solution pH was lowered to pH 6.7 and to a value Ͼ Ͼ 50 nM at pH 6.0, indicating a toxin-like interaction between Bax and the external vestibule of Kv1.3 (Fig.…”
Section: Bax and Kv13 Physically Interactmentioning
confidence: 90%
“…However, we expected this behavior because the orientation of the channel in mitochondria is the same as in the plasma membrane as suggested by the sensitivity of the mitochondrial channel to MgTx (13). Previous studies indicated that the binding of the highly specific Kv1.3 inhibitor toxin (e.g., MgTx), which docks in the outer-facing vestibule of Kv1.3, is pH dependent, and that protonation of Histidine 404 of Kv1.3 weakens the pore-toxin interaction (18). Accordingly, the IC 50 of GST-Bax increased from 4 to 12 nM when the bath solution pH was lowered to pH 6.7 and to a value Ͼ Ͼ 50 nM at pH 6.0, indicating a toxin-like interaction between Bax and the external vestibule of Kv1.3 (Fig.…”
Section: Bax and Kv13 Physically Interactmentioning
confidence: 90%
“…Residue 449 changes from Thr (Shaker) to Tyr (K V 1.1), which might cause a steric-hindrance effect involving Ile23, as was observed for [Ile29]charybdotoxin/[Phe449]Shaker [124]. In contrast, from the study of the toxin blockade of K V 1.3 [44] a favourable interaction between residue 449 and Arg18 can be assumed. Concerning the block- analyses will be necessary to dissect single effects of the residue channels and residues Thr8 and Thr9 [42].…”
Section: Resultsmentioning
confidence: 96%
“…Fig. 9 A shows the position of the residues forming pressed in oocytes) showed the following K d values : charybdo-charybdotoxin [42,44] in agitoxin 2 and cobatoxin 1. Cobatoxin 1 displays a bulky residue in position 4 (Val), which is more voluminous than the equivalent residue in charybdotoxin (Thr).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, DTX-I, MCD-peptide, kaliotoxin and ShK peptide, isolated from snake, bee, scorpion and sea anemone venoms respectively, were of primary importance in characterizing the function of Kv1.1 channels in epilepsy and the contribution of Kv1.3 channels in inflammatory processes (Beeton et al 2001(Beeton et al , 2003Mourre et al 1997). Due to their high specificity and affinity for K + channels, these toxins have facilitated the purification of K + channels, determination of their subunit stoichiometry and sub-cellular localization and tissue distribution (Aiyar et al 1995;Legros et al 2000;MacKinnon 1991;Mourre et al 1986; Rehm and Lazdunski 1988).…”
Section: Potassium Channel Toxinsmentioning
confidence: 99%